Nondifferentiable generalized minimax fractional programming under (phi, rho)-invexity - Upadhyay, Balendu Bhooshan (Yugoslav Journal of Operations Research; Vol 32 No 1 (2022), 2022)
In this paper, a class of nonconvex nondifferentiable generalized minimax fractional programming problems is considered. Sufficient optimality conditions for the considered nondifferentiable generalized minimax fractional programming problem are established under the concept of  (Phi, rho)-invexity. Further, two types of dual models are formulated and various duality theorems relating the primal minimax fractional programming problem and dual problems are established. The results established in the paper generalize and extend several known results in the literature to a wider class of nondifferentiable minimax fractional programming problems. To the best of our knowledge these results have not been established till now.